Income Tax Literacy Article 21 In The KPP Pratama Surakarta Area - Siti Zulaikhah; Rony Arpinto Ady (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Tax literacy is a crucial factor influencing the tax compliance level in a collection system that implements self-assessment. One of the reasons is the low level of compliance of individual taxpayers in Indonesia due to the low level of personal income tax literacy, especially PPh Article 21. This research aims to measure the level of tax literacy for PPh Article 21 in the Surakarta area and its surroundings. The research was conducted using a quantitative approach and data collection techniques using surveys and in-depth interviews. The research results show that the literacy level of PPh Article 21 in Surakarta and its surroundings is moderate. The moderate level of literacy is explained by taxpayers' need for more interest in obtaining information about taxes and the ineffectiveness of tax socialization carried out by the competent tax authorities. There is still a need to optimize the use of social media as a means of tax education for the public to produce efficient and effective tax literacy,